THE USE OF ‘ESTAFET’ METHOD IN IMPROVING STUDENTS’ NARRATIVE WRITING SKILL AT GRADE X OF SMA PERSADA IN ACADEMIC YEAR 2017/2018 - Putri Winda Sari; Dameria Magdalena Sidabalok (Universitas Bandar Lampung, 2017)
This research is based on the researcher’s survey. Most of the students are lack of motivation to write narrative text in their class. It happened because the teachers did not use fun method. Some journals also mentioned that senior high school students have difficulties in writing narrative text because the teachers’ method is not impressive. The researcher chose a method called ‘estafet’ method to overcome the problem. This research is aimed how does the ‘estafet’ method improve students’ narrative writing skill, and to know How is the students’ achievement in writing class through ‘estafet’ method. The sample of this research is SMA Persada students. The data were collected through three stages: observation, questionnaire, and test. The test was performed in the group as a complementary component. The result showed that, ‘estafet’ method can improve the students’ achievement in writing narrative text and the ‘estafet’ method can improve students’ narrative writing skill but the teacher must monitor the students in the class because some students feel confuse about the generic structure of narrative text, so that the teacher must explain again about the generic structure of the narrative text.